The effectiveness of internal control in the payroll accounting system Case Study at PT. Sumber Bahtera Motor Authorized Toyota Yogyakarta - Agung Samudra (Institute of Accounting Research and Novation (IARN), 2023)
This study aims to determine whether the payroll system of PT. Sumber Bahtera Motor Authorized Toyota Yogyakarta is in accordance with theoretical studies that meet the elements of an effective and internal control system. This type of research is a case study. Data collection techniques used were interviews, documentation, and questionnaires. Data analysis techniques were carried out by comparing the theory and practice of the payroll accounting system of PT. Sumber Bahtera Motor Authorized Toyota Yogyakarta to analyze the effectiveness of internal control in the payroll accounting system using the stop-or-go-sampling method. Based on the results of the research and discussion, it shows that the payroll accounting system of PT. Sumber Bahtera Motor Authorized Toyota Yogyakarta is good. The results of the compliance test on the sample did not reveal any deviations or the number of errors was equal to 0 (zero), so AUPL = DUPL, which is 5%. Thus the internal control in the payroll accounting system of PT. Sumber Bahtera Motor Authorized Toyota Yogyakarta has been effective.